2019
DOI: 10.1007/s10973-019-08263-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of time on the heat resistance of self-compacting high-performance concrete incorporated with recycled martials

Abstract: The influence of time on the mechanical behavior of concrete after exposure to elevated temperatures has been studied. Twenty-one self-compacting high-performance concrete mixtures with different incorporation amounts of coarse recycled concrete aggregate (RCA) and three unprocessed waste powder materials have been tested at age of 270 days for residual compressive and flexural strength after exposure to fire. The results have been compared to the results for the same concrete, which have been studied at age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Figure 7 depicts the impact of various cooling procedures on the surface cracking behaviour of concrete specimens following increased temperature exposure for various fire exposure times. The concrete samples developed micro and macro fractures as the temperature and heating duration increased [74]. The fractures developed on the surface of the concrete specimens chilled by spraying water are noticeably broader than those generated on the surface of the concrete cooled by air.…”
Section: Surface Characteristicsmentioning
confidence: 89%
“…Figure 7 depicts the impact of various cooling procedures on the surface cracking behaviour of concrete specimens following increased temperature exposure for various fire exposure times. The concrete samples developed micro and macro fractures as the temperature and heating duration increased [74]. The fractures developed on the surface of the concrete specimens chilled by spraying water are noticeably broader than those generated on the surface of the concrete cooled by air.…”
Section: Surface Characteristicsmentioning
confidence: 89%
“…By studying the effect of time on concrete performance after exposure to high temperatures, it has been found by the authors (Abed et al, 2019) that the heat resistance of compressive strength can be enhanced or slightly decrease with age, but the concrete (at the age of 270 days) behaved differently than at the age of 90 days. Heat resistance is a new parameter called heat resistance introduced by authors to express the total area under the curve of the relative residual strength (20-800 8C).…”
Section: Fire Resistance Of Recycled Aggregate Concretementioning
confidence: 99%
“…By studying the effect of time on concrete performance after exposure to high temperatures, it has been found by the authors (Abed et al. , 2019) that the heat resistance of compressive strength can be enhanced or slightly decrease with age, but the concrete (at the age of 270 days) behaved differently than at the age of 90 days.…”
Section: Fire Resistance Of Recycled Aggregate Concretementioning
confidence: 99%
“…Moreover, it is beneficial in segmenting the crack elongation and filling the large pores which is valuable for bending resistance [36]. Farzadnia et al [37] found that titanium (TiO 2 ) improved the residual strength after high temperatures exposure [38]. A dosage of 2 g/kg of liquid superplasticizer (GLENIUM ® C 300 (AT)) was applied for each mix.…”
Section: Deterioration Of Microstructure and Crackingmentioning
confidence: 99%